THE ORBIT, ATMOSPHERIC DYNAMICS, AND INITIAL MASS OF THE PARK FOREST METEORITE - Brown P.; Pack D.; Edwards W.N.; ReVelle D.O.; Yoo B.B.; Spalding R.E.; Tagliaferri E. (My University, 2004)
The fireball accompanying the Park Forest meteorite fall (L5) was recorded by ground‐based videographers, satellite systems, infrasound, seismic, and acoustic instruments. This meteorite shower produced at least 18 kg of recovered fragments on the ground (Simon et al. 2004). By combining the satellite trajectory solution with precise ground‐based video recording from a single site, we have measured the original entry velocity for the meteoroid to be 19.5 ± 0.3 km/s. The earliest video recording of the fireball was made near the altitude of 82 km. The slope of the trajectory was 29° from the vertical, with a radiant azimuth (astronomical) of 21° and a terminal height measured by infrared satellite systems of 18 km. The meteoroid's orbit has a relatively large semi‐major axis of 2.53 ± 0.19 AU, large aphelion of 4.26 ± 0.38 AU, and low inclination. The fireball reached a peak absolute visual magnitude of −22, with three major framentation episodes at the altitudes of 37, 29, and 22 km. Acoustic recordings of the fireball airwave suggest that fragmentation was a dominant process in production of sound and that some major fragments from the fireball remained supersonic to heights as low as ˜10 km. Seismic and acoustic recordings show evidence of fragmentation at 42, 36, 29, and 17 km. Examination of implied energies/initial masses from all techniques (satellite optical, infrasound, seismic, modeling) leads us to conclude that the most probable initial mass was (11 ± 3) × 103 kg, corresponding to an original energy of ˜0.5 kt TNT (2.1 times 1012 J) and a diameter of 1.8 m. These values correspond to an integral bolometric efficiency of 7 ± 2%. Early fragmentation ram pressures of <1 MPa and major fragmentations occurring with ram pressures of 2–5 MPa suggest that meter‐class stony near‐Earth asteroids (NEAs) have tensile strengths more than an order of magnitude lower than have been measured for ordinary chondrites. One implication of this observation is that the rotation period for small, fast‐rotating NEAs is likely to be >30 seconds.